2012
DOI: 10.1007/s00127-012-0483-z
|View full text |Cite
|
Sign up to set email alerts
|

Case managers’ perspectives on the therapeutic alliance: a qualitative study

Abstract: The current qualitative findings suggest that current constructions and measures of the therapeutic alliance developed in psychotherapy research are not fully capturing the ways in which the unique structure and constraints of intensive case management influence relationships between workers and consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Expressed emotion in relationships between psychiatric staff and people with psychosis tends to be low, but high frequency of contacts is associated with difficulties in keeping professional distance . The EIPS model involves assertive outreach and an intense 3‐year relationship with a key worker, and we know that concerns about the development of dependency on ongoing emotional support are common during the first 9 months of a therapeutic relationship …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expressed emotion in relationships between psychiatric staff and people with psychosis tends to be low, but high frequency of contacts is associated with difficulties in keeping professional distance . The EIPS model involves assertive outreach and an intense 3‐year relationship with a key worker, and we know that concerns about the development of dependency on ongoing emotional support are common during the first 9 months of a therapeutic relationship …”
Section: Discussionmentioning
confidence: 99%
“…46 The EIPS model involves assertive outreach and an intense 3-year relationship with a key worker, and we know that concerns about the development of dependency on ongoing emotional support are common during the first 9 months of a therapeutic relationship. 47 Increased key worker emotional involvement in the form of worry and tension may be understood as secondary to transference: clinicians working with clients with PD report thoughts, feelings, motivations and behaviours that reflect the client's enduring patterns of relating to others, 48,49 especially among professionals who have not received specialist training. 50 Other explanations may lie in the higher frequency of early traumatic experiences (e.g.…”
Section: Formulating Key Worker Emotional Involvementmentioning
confidence: 99%
“…Writings on recovery also describe the detrimental impact of directive or coercive relationships between mental health providers and adults living with mental illness Farkas et al 2005). However, factors that shape the nature of professional relationships between consumers and providers working in a recovery model of service delivery are not well understood (Nath et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been suggested that the mental health care context can elicit patients’ dependency on professional treatments. For example: as a result of the identification of new psychological disorders by mental health care professionals, or the institutions that make help available on demand for 24/7, or the need of psychotherapists to be needed (e.g., Berk & Parker, ; Bressi Nath, Alexander, & Solomon, ; Bystedt, Rozental, Andersson, Boettcher, & Carlbring, ; Clemens, ; Hutschemaekers, ; Leitner et al., ; Linden, ; Tait, ).…”
mentioning
confidence: 99%